Synthesis, Characterization, and Photocatalytic Performance of ZnFe2O4-g-C3N4 Composites for Tetracycline Removal from Contaminated Water - Humphrey Mutuma Samuel; Milton M. M’Arimi; Cleophas Achisa Mecha (Journal of Nanotechnology)
The presence of emerging contaminants in wastewater like tetracycline poses a significant challenge in water reuse worldwide. The implementation of a p-n heterojunction and dye-sensitized techniques in the enhancement of graphite carbon nitride provides a promising alternative for visible light-driven degradation of emerging contaminants present in wastewater. The present study investigated dye-sensitized and plain composites in degrading tetracycline using natural sunlight in a parabolic trough reactor. The study synthesized four composites of ZnFe2O4-g-C3N4 at 5, 15, and 25 wt% loading of the ferrite by direct annealing of melamine, followed by thermal and ultrasonic exfoliation of bulk graphite carbon nitride and in situ precipitation with zinc ferrites to yield a composite photocatalyst. The photocatalysts were characterized using X-ray diffraction (XRD) analyses which confirmed that all the spinel ferrite phases of ZnFe2O4 were well bonded with g-C3N4 nanosheets to form a composite. The crystallite sizes were calculated by the Debye–Scherrer equation indicating crystal sizes of between 4.63 and 8.61 nm confirming the nanostructures. The scanning electron microscope-energy dispersive spectroscopy (SEM-EDX) tests verified that the spherical globules of ZnFe2O4 were well attached to the mesoporous layers of g-C3N4 and absence of contaminant phases. The UV-Vis analysis for 25% ZF-GCN revealed a band gap reduction from 2.67 eV to 2.03 eV. The PL intensity for all the composites decreased at excitation of 266 nm and 550 nm which was evidence for suppressed charge recombination. A 25% ferrite loading resulted in the best photocatalytic performance with tetracycline degradation of 93.64% and total organic carbon (TOC) removal of 51.89%. The sensitization of the 25% ZF-GCN composite with Eosin Y further improved its performance for degradation of tetracycline to 94.62% and TOC removal to 68.29%. Therefore, dye sensitization is an efficient way of improving the photocatalytic activity of a multicomponent photocatalyst for the removal of emerging pollutants.